A Case of Leiomyosarcoma of the Kidney - Adhikari, R.C.; Sayami, G.; Dali, S.; Shrestha, H.G. (Journal of Institute of Medicine Nepal, 2007)
Introduction: Sarcomas of the kidney are rare. Among primary sarcomas, leiomyosarcoma is the most frequent. A case of primary renal leiomyosarcoma is presented. Case report: This report concerns a 48 year old women, who presented with slowly increasing right flank mass and dull aching pain. A well defined, gray, firm mass measuring 12.5x10.5 cm was histologically composed of interlacing bundles of spindle cells with cellular atypia and nuclear hyperchromasia. Mitotic figures constituted 10-12/10 HPF. Tumor cells showed positivity for desmin. The differentiation from sarcomatoid renal cell carcinoma is discussed. Conclusion: The case is reported for its rarity and this is the first reported case of renal leiomyosarcoma in Nepal. Journal of Institute of Medicine Vol.28(1) 2006